2014
DOI: 10.1155/2014/728198
|View full text |Cite
|
Sign up to set email alerts
|

Giant Bilateral Adrenal Myelolipoma with Congenital Adrenal Hyperplasia

Abstract: Myelolipomas are rare and benign neoplasms, predominant of the adrenal glands, consisting of adipose and mature hematopoietic tissue, commonly discovered incidentally with increased use of radiologic imaging. Few cases of giant bilateral adrenal masses are reported, especially in the setting of congenital adrenal hyperplasia (CAH). We report the case of a 39-year-old male with a history of CAH secondary to 21-α hydroxylase deficiency on steroids since childhood, self-discontinued during adolescence, presenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 31 publications
1
33
0
7
Order By: Relevance
“…Frequently they are unilateral, and smaller than 4 cm, and tend to develop in the adrenal gland (right/left ratio: 3/2). However bilateral and giant adrenal myelolipomas have been also reported in the literature (2,3) . As far as we knew, the largest adrenal myelolipoma cited in the literature was 40 cm in diameter (4) .…”
Section: Discussionmentioning
confidence: 99%
“…Frequently they are unilateral, and smaller than 4 cm, and tend to develop in the adrenal gland (right/left ratio: 3/2). However bilateral and giant adrenal myelolipomas have been also reported in the literature (2,3) . As far as we knew, the largest adrenal myelolipoma cited in the literature was 40 cm in diameter (4) .…”
Section: Discussionmentioning
confidence: 99%
“…This metaplasia may occur as a response to necrosis, stress, infections, or prolonged adrenocorticotropic hormone (ACTH) stimulation 11, 18 . For example, Al-Bahri et al 19 reported a case of a large bilateral myelolipoma in a 39 year old male with a history of congenital adrenal hyperplasia secondary to a 21-α hydroxylase deficiency treated with steroids starting in childhood. This was later stopped during adolescence with a subsequent myelolipoma development - supporting the theory that ACTH stimulation causes adrenocortical metaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 20% of AIs will have subclinical hormone production and these patients represent an at-risk population with greater risk of metabolic disorders and cardiovascular disease 7, 19 . In the present case, the patient’s hormone values were within normal parameters - ruling out subclinical states, including Conn's Syndrome (hyperaldosteronism), Cushing Syndrome or pheochromocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…Though rare, bilateral myelolipomas have been described in literature. [7][8][9][10][11][12][13] Myelolipomas are usually of small size often less than 4 cm diameter. Majority of the patients are asymptomatic but it can attain very large size and cause symptoms.…”
Section: Discussionmentioning
confidence: 99%